1984
DOI: 10.1038/307074a0
|View full text |Cite
|
Sign up to set email alerts
|

Bonding of molecular oxygen to T state human haemoglobin

Abstract: Haemoglobin (Hb) is the tetrameric protein molecule that in vertebrate blood transports oxygen from the lungs to the tissues. This function depends on four subunits in the molecule binding cooperatively so that their affinity for oxygen increases as the level of oxygenation increases. X-ray analysis has shown that deoxyhaemoglobin, which has a low oxygen affinity, and oxyhaemoglobin, which has a high oxygen affinity, differ principally in their subunit or quaternary structures, referred to as the T and R state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
2

Year Published

1987
1987
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(51 citation statements)
references
References 13 publications
3
46
2
Order By: Relevance
“…¶ This notation identifies the fully liganded R2 state of human Hb. spite the extensive use of a variety of experimental techniques (19,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). In this context, the mixed structure of HbTn[␣(CO)␤(hemi)] 2 herewith reported displays a number of interesting features.…”
Section: Discussionmentioning
confidence: 89%
“…¶ This notation identifies the fully liganded R2 state of human Hb. spite the extensive use of a variety of experimental techniques (19,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). In this context, the mixed structure of HbTn[␣(CO)␤(hemi)] 2 herewith reported displays a number of interesting features.…”
Section: Discussionmentioning
confidence: 89%
“…In the past 10 years, it has become possible to crystallize Hb under conditions where the crystals do not shatter upon changing the degree of ligation. In this method, deoxygenated Hb A was crystallized from solutions of polyethylene glycol (28,29) and the X-ray crystal structures showed that the molecules remained in the T state and that the salt bridges remained intact over the full range of oxygen tension from 9 to 700 Torr. The crystallographic results surprisingly showed that only the ® chains were ligated even at the high oxygen pressure.…”
Section: Do the Salt Bridges Break Upon Ligation?mentioning
confidence: 99%
“…We will also compare the energetics with crystallographic results (3,4 (6)(7)(8). The thermodynamic coupling between ligand binding and reversible dissociation of tetramers into dimers has thus proved to be a powerful means of measuring cooperative free energies (5)(6)(7)(8).…”
mentioning
confidence: 99%